2020
DOI: 10.36517/revpsiufc.11.1.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Elementos caracterizadores das representações sociais da amizade para universitários

Abstract: Dentre as modalidades de relacionamentos interpessoais, a amizade desponta como uma das mais significativas, considerando os valores e comportamentos associados ao que se espera em uma relação de amizade. O objetivo deste estudo foi identificar os elementos caracterizadores das representações sociais da amizade para universitários. Compôs a amostra 120 estudantes, de ambos os sexos, tendo sido utilizada uma entrevista semidiretiva para a coleta dos dados, complementada por questões de caracterização da amostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…Elas também elencaram o amor e a paixão mútua, como motivos para o casamento (Moraes, Ortega, Alencar & Galvão, 2019). Universitários citaram que o amor e a paixão são essenciais para o início e a manutenção dos relacionamentos amorosos (Schlösser & Camargo, 2019). Por sua vez, casais estadunidenses expuseram a paixão como qualidade da relação conjugal deles (Gildersleeve et al, 2017).…”
Section: Descrição E Discussão Dos Resultadosunclassified
See 1 more Smart Citation
“…Elas também elencaram o amor e a paixão mútua, como motivos para o casamento (Moraes, Ortega, Alencar & Galvão, 2019). Universitários citaram que o amor e a paixão são essenciais para o início e a manutenção dos relacionamentos amorosos (Schlösser & Camargo, 2019). Por sua vez, casais estadunidenses expuseram a paixão como qualidade da relação conjugal deles (Gildersleeve et al, 2017).…”
Section: Descrição E Discussão Dos Resultadosunclassified
“…Os participantes aludiram à busca por uma relação amorosa estável, como uma das principais razões para o casamento (Emídio & Souza, 2019). As depoentes dos estudos de Galvão, Alencar e Alves (2017 Em uma pesquisa realizada com 120 jovens universitários, de ambos os sexos, os discentes explicaram que o amor e a paixão são fundamentais para o início e a conservação dos relacionamentos amorosos (Schlösser & Camargo, 2019). Nos Estados Unidos, indagaram-se 53 casais acerca da conjugalidade deles.…”
unclassified
“…Consequently, tolerance to differences can also designate the importance of the process of openness to the other, through differences and questions. 20 Nevertheless, the entry into higher education is a transition that brings potential repercussions for the psychological development of young students. Initially, it represents the first important attempt to implement a sense of autonomous identity through professional choice, a typical task of development in the transition from adolescence to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…15 In such a way, the trustworthy alliance refers to loyalty, availability; self-assessment consists of reassuring, encouraging and helping others to maintain a positive self-image; and, emotional security is about providing comfort and confidence in new or threatening situations. 15 In view of this, in a research carried out by Schlösser, 16 it was found that friendly relationships are sustained by the perception of wellbeing and quality of life, being one of the attributes considered essential in other types of relationships, such as loving ones. It was also analyzed that one of the elements to maintain friendship, concerns tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that tolerance is one of the characteristic elements associated with care in the friendship relationship, it is about the sense of having patience in the face of differences. 16 It refers to a necessary condition that is extremely important in friendship relationships, for so that the relationship is long lasting. 14 Furthermore, it is possible to affirm that the difficulties experienced by health workers in the midst of the pandemic, both related to work itself, and related to personal and individual issues of affective relationship and the daily fear of being contaminated or transmitting the disease to loved ones, they are very conflicting situations.…”
Section: Introductionmentioning
confidence: 99%